Redundancy-based intrusion tolerance approaches moving from classical fault tolerance methods - Di Giandomenico, Felicita; Masetti, Giulio; Chiaradonna, Silvano (Zielona Góra: Uniwersytet Zielonogórski)
Borrowing from well known fault tolerant approaches based on redundancy to mask the effect of faults, redundancy-based intrusion tolerance schemes are proposed in this paper, where redundancy of ICT components is exploited as a first defense line against a subset of compromised components within the redundant set, due to cyberattacks. Features to enhance defense and tolerance capabilities are first discussed, covering diversity-based redundancy, confusion techniques, protection mechanisms, locality policies and rejuvenation phases.
Keywords: intrusion tolerance; cyberattack; diversity-based redundancy; protection mechanisms